Excessive use of nitrogen causes monetary loss For coffee growers in the cerrado - Pinto, Victor Meriguetti; Bruno, Isabeli Pereira; de Jong van Lier, Quirijn; Dourado Neto, Durval; Reichardt, Klaus (Coffee Science - ISSN 1984-3909, 2017)
Fertilizers used in excess may harm the environment and increase the costs of crop production. The present study aimed to predict the monetary expenditure related to nitrogen (N) losses by leaching, volatilization and denitrification in a fertigated coffee plantation in the Cerrado, and also to bring up the advantages of reducing N rates applied in such an agroecosystem. SWAP and ANIMO models were used to simulate the N balances for a simulated area of coffee cultivation managed with rates of 200, 300, 400 and 600 kg ha-1 y-1 of N. The average annual investment for coffee production varied from 36.1 to 65.3 thousand BR-Real per pivot, and the expenses with soil and canopy N storage were 13.6 to 85.3 thousand BR-Real. The average annual expenses with N leaching by pivot were between 7.5 to 25.4 thousand BR-Real, and with volatilization and denitrification between 4.4 to 8.8 thousand BR-Real. Reducing the N rate employed for coffee plants from 600 kg ha-1 y-1 of N to 400 kg ha-1 y-1 of N, would diminished by 33% the costs of N fertilizer application, by 46% the expenses with N leaching and by 26% the expenses with nitrogenous compoundsloss to the atmosphere.